Energy follows thought the stories behind my songs - Nelson, Willie 1933-; Ritz, David 1943-; Raphael, Mickey (William Morrow, 2023)
For the first time ever, and to help celebrate his 90th birthday in 2023, American icon Willie Nelson provides the stories behind the lyrics of 160 of his favorite songs, along with a dynamic assortment of never-before-seen photos and ephemera. From his earliest work in the 1950s to today, Willie looks back at the songs that have defined his career, from his days of earning $50 each to his biggest hits, from his less well-known songs (but incredibly meaningful to him) to his concept albums. Along the way, he also shares the stories of his guitar Trigger, his family and "family," as well as the artists he collaborated with, including Patsy Cline, Waylon Jennings, Ray Charles, Merle Haggard, Ray Price, Dolly Parton, and many others. Willie is disarmingly honest--what do you have to lose when you're about to turn 90? --meditating on the nature of songwriting and finding his voice, and the themes he's explored his whole life--relationships, infidelity, love, loss, friendship, life on the road, and particularly poignant at this juncture of his life: mortality. Revealing, funny, whimsical, and wise, this book is an enduring tribute to Willie Nelson's legacy. --
Includes index
Keywords: Nelson, Willie -- 1933-; Nelson, Willie / 1933- / Discography; Nelson, Willie / 1933- / Pictorial works; Country music; MUSIC / Genres & Styles / Country & Bluegrass; BIOGRAPHY & AUTOBIOGRAPHY / Music; Nelson, Willie / 1933-; photobooks; Discographies; Photobooks; Illustrated works; Livres de photographies; Ouvrages illustrés; Autobiografie